Physiological, Nutritional, and Other Disorders of Tomato Fruit - Stephen M. Olson (EDIS)
Tomato producers run into many different fruit problems each year. This publication attempts to describe, give possible causes or explanations, and possible controls for certain of these tomato fruit problems. This document is HS-954, one of a series of the Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: February 2004.